Comparative study: Activity based costing and time driven activity based costing in electronic industry - Nurul Farahin, Zamrud; Mohd Yazid, Abu (Penerbit UMP, 2020)
By the 1980s, Traditional Cost Accounting (TCA) is no longer reflecting the current economic reality due to distorted information about the profitability of their orders, products, and customers. In addition, Activity-based Costing (ABC) is a costing method originally developed to overcome the shortcoming of TCA method in the era of rapidly increasing product complexity and diversification. However, it is not universally accepted because it ignores the potential for unused capacity which will be beneficial for forecasting. The objective of this work is to compare the advantages of ABC and Time-driven Activity-Based Costing (TDABC) by analyzing the features towards costing sustainment. The work begins by collecting data at electric electronic industry located at Pahang and the product selected is a magnetic inductor. ABC focuses on the costs inherent in the activity based products to produce, distribute or support the products concerned. TDABC uses time equation and capacity cost rate (CCR) to measure the unused capacity with respect to the time and cost. This work has successfully compares the methodology between ABC and TDABC in electronic industry. The item such as stages for cost allocation, determination of drivers, action taken for an additional activity, cost consideration for implementation, system building, system update, information given from each method, transparency, overestimation of cost, differentiation of service level, oversimplification of activities and capacity forecast and planning. It concludes that both have their strength according to the industry needs.